MXD3 as an Immunological and Prognostic Factor From Pancancer Analysis - Zhang, Xiaoyu; He, Xiaoqin; Li, Yue; Xu, Yangtao; Chen, Wenliang; Liu, Xin; Hu, Xinyao; Xiong, Lin; Xu, Ximing (Frontiers in Molecular Biosciences, 2021)
Abstract: MAX dimerization protein 3(MXD3), as a transcriptional regulator of MXD3 superfamily, is a part of MYC-MAX-MXD network. However, its role in tumors has been reported only in B-cell acute lymphoblastic leukemia, medulloblastoma, neuroblastoma and glioblastoma, but other cancers have not been mentioned yet. Based on the data of TCGA and GEO, our first pan-cancer study of MXD3 confirmed the high expression of MXD3 in cancer tissues, and our result uncovered that patients suffering from cancers with higher MXD3 expression had poor OS, DSS, DFI and PFS totally. We further explored the methylation status of the MXD3 gene body and gene promoter in cancer. Patients with higher MXD3 gene body have better OS, while the prognosis of high MXD3 premotor had more complex status. We also verified the differential expression of three clinical phenotypes of MXD3: age, gender and tumor stage in a variety of tumors, suggesting the correlation between MXD3 and clinical characteristics. We explored the negative relationship between MXD3 and TMB and MSI in most types of cancer. which indicated the bad prognosis of patients with high MXD3 expression. We further investigated the relationship between MXD3 and immune infiltrating cells and identified the relationship between MXD3 and immune genes, immunosuppressive genes, and antigen-presenting genes. All above established a solid relationship between MXD3 and immune environment and immune cells, proved that MXD3 may be a potential immune factor as well. We also discovered the higher expression of MXD3 and premotor according to the rising of glioma WHO grade or histologic types. Glioma patients with high MXD3 or MXD3 premotor expression had poor survival. Finally, we used IHC to verified the high expression of MXD3 in glioma samples compared with normal samples. Our study shows that MXD3, as a poor prognostic factor, plays a significant role in many cancers, especially glioma. Although more clinical evidence is needed as a clinical therapeutic target and immunotherapy site, it can play an important guiding role in a variety of clinical treatments including immunotherapy and demethylation therapy.